2011
DOI: 10.1007/s00264-011-1403-7
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical values of the normal and arthritic hip and knee detected with the EOS imaging system

Abstract: EOS 2D/3D with its sterEOS 3D reconstruction is useful for a comprehensive 3D examination of the lower limb. In the near future it may be suitable for daily routine diagnostics of orthopedic lower limb deformities as a primary examination method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 17 publications
1
39
1
3
Order By: Relevance
“…Stratified by pincer size, rotation, and tilt, the intermodality ICCs showed excellent reliability between EOS 1 and conventional radiography in morphologic features of the pincer. Our study also is consistent with previous EOS 1 imaging studies, which all showed an image quality of EOS 1 comparable to improved compared with that of conventional radiography [1,6,17,18,20,24,31]. However, we did see relative horizontal widening of the image in EOS 1 with extreme anterior tilt (C 10°) and horizontal narrowing in extreme posterior tilt (C 10°) owing to the decrease or increase in distance between the x-ray beam and the pelvis (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Stratified by pincer size, rotation, and tilt, the intermodality ICCs showed excellent reliability between EOS 1 and conventional radiography in morphologic features of the pincer. Our study also is consistent with previous EOS 1 imaging studies, which all showed an image quality of EOS 1 comparable to improved compared with that of conventional radiography [1,6,17,18,20,24,31]. However, we did see relative horizontal widening of the image in EOS 1 with extreme anterior tilt (C 10°) and horizontal narrowing in extreme posterior tilt (C 10°) owing to the decrease or increase in distance between the x-ray beam and the pelvis (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…EOS 1 imaging uses a slot scanner that creates a horizontal fan beam and then physically moves vertically to capture the designated body part [6] as opposed to conventional radiography which uses a fixed cone beam [3]. Radiation doses of EOS 1 have been reported as eight to 10 times less than conventional radiography and 800 to 1000 times less than CT [15,20,31]. A couple studies have validated the use and reliability of EOS 1 in imaging of the hip and lower extremities [18,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the authors' knowledge, only three studies have quantified morphological parameters in non-OA and OA subjects in the standing position (Okuda et al, 2007;Than et al, 2012;Yoshimoto et al, 2005); however each has limitations. In the first study, the non-OA group had low back pain and only the sagittal-plane pelvic parameters were evaluated; in the second study, the OA group consisted only of females with hip OA secondary to acetabular dysplasia and again only the 2D pelvic parameters were evaluated; and in the third study only the lower limb parameters were evaluated.…”
Section: Introductionmentioning
confidence: 97%
“…7) [12]. Horizontal plane rotational aspects of the whole skeletal system are readily visualised and evaluated in top-view images.…”
Section: Introductionmentioning
confidence: 99%